Management problems in turner syndrome: towards early recognition and improved outcome - Waduge, T.R.W.; Pradeepan, M.; Wijeyaratne, C.N. (My University, 2003)
BACKGROUND: Girls with Turner syndrome are at risk of problems other than hypogonadism and short stature. OBJECTIVE: To determine management problems encountered in the long-term follow up of a cohort of women with Turner Syndrome. METHOD & DESIGN: Observational case series. RECRUITMENT: Consecutive women diagnosed with Turner Syndrome managed in a specialist Endocrine Clinic, Colombo. OUTCOME MEASURES: Age at diagnosis, mode of diagnosis, physical stigmata, prevalence of short stature, cardiac, renal, orthopaedic and metabolic problems encountered, hormone replacement and psycho-social issues RESULTS: Sixteen women with Turner Syndrome with a mean duration of follow up of 5.7 years (range 1-10) are reported. Median age at diagnosis 20.5 (range 1 -25) years with 12 (75 percent) presenting with primary amenorrhoea. Karyotype 45X0 in 6 (37.5 percent) while 8 had ultrasound evidence and 7 required diagnostic laparoscopy to confirm streaky gonads. Nine (56 percent) had <2SD height, of whom two were treated with synthetic growth hormone pre-HRT therapy. Physical stigmata included nail dysplasia (44 percent), low hairline (63 percent), low set ears (63 percent), webbed neck (38 percent) and shield chest (38 percent). One had bicuspid aortic valves, 3 others horseshoe kidneys and another solitary kidney. Average BMI 24+0.8 kg/m2. Hypothyroidism developed in 5 (31 percent), diabetes mellitus in 01, hypertension in 4 (25 percent) and osteoporosis was evident in 8 (50 percent), with three having a fracture during HRT and follow up. 50 percent dropped out of primary school with 3/6-drop outs from secondary school, while one is currently an undergraduate. 4/10 over the age of 20 are in unskilled employment. CONCLUSIONS & RECOMMENDATIONS: This data, while confirming that Turner syndrome is not confined to growth and gonadal problems, highlights the importance of long term follow up by a multi-disciplinary team that encompasses issues related to endocrinology, osteoporosis, reproductive and psycho-social aspects.
Keywords: TURNER SYNDROME